Hypertensive Crisis: Clinical-epidemiological Characterization and Cardiovascular Risk Stratification - Grissel Utrera Díaz; Lianet Pérez Rodríguez; Pedro Toledo Yanes (Universidad de las Ciencias Médicas de Cienfuegos, 2021)
Background: cardiovascular diseases and among them arterial hypertension constitutes one of the most important causes of disability and premature death worldwide. Objective: to determine the clinical-epidemiological characteristics and the global cardiovascular risk of patients with hypertensive crisis at the Cecilio Ruiz de Zárate Comunitary University Polyclinic in Cienfuegos during June 2018 - May 2019. Methods: a descriptive, prospective, longitudinal study was carried out in the guardhouse of the Cienfuegos municipality Cecilio Ruiz de Zarate Comunitary University Polyclinic since June 2018 to May 2019. The variables analyzed were: age group, sex, type of hypertensive crisis, time of evolution of the disease, clinical stage, medical treatment, smoking habit, presence of diabetes mellitus and cholesterol levels to determine the global cardiovascular risk that was stratified in low ( = 40 %. The data were processed with the statistical package SSPS v. 19.0 and presented in tables with numbers and percentages. Results: the 91.7 % had a hypertensive emergency and 8 % had a hypertensive emergency. The age group of 50-59 years old of the male sex prevailed, 72.6 % were smokers, 39.7 % were diabetic and 31.5 % with high cholesterol. Most of them are stage II of the disease and without medical or inadequate treatment, with a large number of patients with moderate global cardiovascular risk and high risk. Conclusions: there were deficiencies in the management and control of arterial hypertension, as well as a large number of patients at risk of suffering a cardiovascular event in the next 10 years.